DSP-based fuzzy logic controller for a battery charger - Chan, E.L.; Rahim, N.A.; Mekhilef, Saad (2002)
The DSP-based fuzzy logic controller for a battery charger has been investigated in this paper. The conventional battery charger experiences a highly distorted current harmonic waveform and low power factor. Thus, the proposed battery charger with a fuzzy logic controller to improve the line power quality and deliver maximum allowable output power to the battery. The fuzzy control algorithm is implemented with the Digital Signal Processor (DSP) to optimize a fuzzy rule-based system to produce the desired output. The TMS320C5x DSP is employed to supply the pulse width modulation (PWM) waveforms and to perform the fuzzy control feedback. The PWM waveforms are required to generate gating signals for the converters. The DSP-based fuzzy controller in turn provides control over the PWM pattern. The fuzzy controller continuously monitors the state of battery and controls the PWM accordingly. This simple and reliable DSP-based fuzzy control provides an easier implementation and optimum performance for the battery charger.